Multiple environmental signals determine the transcriptional activation of the mycoparasitism related gene prb1 in Trichoderma atroviride - Olmedo Monfil, V; Mendoza Mendoza, A; Gomez, I; Cortes, C; Herrera Estrella, A (Molecular genetics and genomics : MGG, 2002)
Trichoderma atroviride parasitizes a large variety of phytopathogenic fungi. This characteristic has allowed its use as a biological control agent. The production of hydrolytic enzymes appears to be a key element in the parasitic process. Among the enzymes released by Trichoderma, the proteinase Prb1 plays a major role. We show here that the corresponding gene ( prb1) is subject to nitrogen catabolite repression. Accordingly, induction of prb1 transcription by Rhizoctonia solani cell walls and by osmotic stress requires release from a repressed condition, which is determined by nitrogen availability. Furthermore, the transcription pattern of the prb1 gene was not affected when an inhibitor of p38-Hog1, a regulator of the response to osmotic shock, was used. In contrast, a MEK1/2 (MAPK/ERK) inhibitor blocked prb1 transcription in response to nitrogen limitation, indicating that the pathway employed in the nitrogen response involves proteins similar to p42-p44. Fusion of the prb1 promoter to the gfp reporter gene allowed the detection of a novel regulatory element, providing an initial insight into the nature of the sites that control prb1 expression.